An Experimental Look at Bracket-Loaded Webs - Ainso, Heino; Hoptay, Joseph M. (Engineering Journal, 1981)
Brackets attached rigidly to the web of a rolled member require a check of the bending stresses in the web in order to avoid overstressing or tearing of the web. Figure 1 describes a typical bracket attachment. No guidance for sizing the web is found in the AISC Specification, but Abolitz and Warner have presented a theoretical yield line analysis for bending under seated connections that estimates the capacity of the web. Their method of analysis yielded a very simple and elegant upper bound solution. This paper compares some experimental data with the theoretical solution proposed by Abolitz and Warner, in order to assess the applicability and safety of an upper bound solution. The results of the test program, although limited, verified the soundness of the collapse mechanism approach of plastic analysis as proposed by Abolitz and Warner, for the design of bracket-to-web column connections. However, since Abolitz and Warner did not perform any tests, their recommended design procedure is still conservative.